THE THE RELEVANCE OF ACCOUNTING INFORMATION VALUE WITH HUMAN CAPITAL AS A MODERATION VARIABLE - Tambunan, Indah Meilani Pramesti; Kuswanto, Randy (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The purpose of this study is to examine the influence of the value relevance of accounting information on human capital as a moderator. Methods: This study analysed secondary data available on the Indonesia Stock Exchange (IDX) in 2022-2023. Data analysis was performed using multiple linear regression and moderation regression, supported by SPSS software.Results: The results of this study indicate that value relevance, as measured by profit and book value of equity indicators, significantly influences company value in the financial sector and is reinforced by competent human capital as a moderating variable. Therefore, this study provides a new perspective by emphasising the importance of accounting information, indicating that companies with high human capital tend to be better able to utilise accounting information to improve their performance and competitiveness. Unlike previous studies that view human capital as part of intellectual capital, this study specifically treats human capital as a moderating variable, making essential contributions to the accounting and human resource management literature, as well as providing practical implications for companies in managing human resources and accounting information more effectively. Keywords: Value relevance, Earnings Per share, Book value per share, firm value and human capital.